Managing innovation: a qualitative study on the implementation of telehealth services in rural emergency departments - Mochamad Muska Nataliansyah; Kimberly A. S. Merchant; James A. Croker; Xi Zhu; Nicholas M. Mohr; James P. Marcin; Hicham Rahmouni; Marcia M. Ward (BMC, 2022)
Abstract Background Telehealth studies have highlighted the positive benefits of having the service in rural areas. However, there is evidence of limited adoption and utilization. Our objective was to evaluate this gap by exploring U.S. healthcare systems' experience in implementing telehealth services in rural hospital emergency departments (TeleED) and by analyzing factors influencing its implementation and sustainability. Methods We conducted semi-structured interviews with 18 key informants from six U.S. healthcare systems (hub sites) that provided TeleED services to 65 rural emergency departments (spoke sites). All used synchronous high-definition video to provide the service. We applied an inductive qualitative analysis approach to identify relevant quotes and themes related to TeleED service uptake facilitators and barriers. Results We identified three stages of implementation: 1) the start-up stage; 2) the utilization stage; and 3) the sustainment stage. At each stage, we identified emerging factors that can facilitate or impede the process. We categorized these factors into eight domains: 1) strategies; 2) capability; 3) relationships; 4) financials; 5) protocols; 6) environment; 7) service characteristics; and 8) accountability. Conclusions The implementation of healthcare innovation can be influenced by multiple factors. Our study contributes to the field by highlighting key factors and domains that play roles in specific stages of telehealth operation in rural hospitals. By appreciating and responding to these domains, healthcare systems may achieve more predictable and favorable implementation outcomes. Moreover, we recommend strategies to motivate the diffusion of promising innovations such as telehealth.